1994
DOI: 10.1111/j.1464-410x.1994.tb16613.x
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variations in the risk of urinary calcium oxalte stone formation

Abstract: The lithogenic risk for calcium oxalate stones was maximal at the end of the night or during the early morning, when urinary output was minimal. This circadian study revealed abnormalities that are not apparent from non-fractionated 24 h urine samples, and which were potentially relevant to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…This rhythm means that urine is hyperconcentrated during night time, which entails a risk of nephrolithiasis and infections. The lithogenic risk for calcium oxalate stones is highest at the end of the night or during the early morning, when urinary output is minimal 3. Studies on healthy people and people who have had kidney stones showed a higher risk of calcium oxalate crystallisation in the morning 4.…”
Section: Commentmentioning
confidence: 99%
“…This rhythm means that urine is hyperconcentrated during night time, which entails a risk of nephrolithiasis and infections. The lithogenic risk for calcium oxalate stones is highest at the end of the night or during the early morning, when urinary output is minimal 3. Studies on healthy people and people who have had kidney stones showed a higher risk of calcium oxalate crystallisation in the morning 4.…”
Section: Commentmentioning
confidence: 99%
“…Most, if not all, renal functions (e.g., glomerular filtration, urine production, and renal solute excretion) exhibit temporal changes that lead to increased nighttime urine concentration that could act as a predisposing factor for the morning occurrence of renal colic attacks. In addition, the rates of urine production and renal solute excretion reach minimum levels during the night [24]. For this reason, our study showed the highest peak during the morning.…”
Section: Discussionmentioning
confidence: 53%
“…Superimposed upon these considerations are circadian rhythms of calcium, oxalate, and phosphate, which have been shown to aVect saturation and lithogenic risk. [53][54][55] We recommend that these factors should be explored in terms of the eVects of calcium supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Although urine phosphate appeared to be higher in the summer, there were no significant seasonal differences in 246 male stone formers in observations by Robertson,35 and there were no diVerences in a study of UK doctors, 36 or in 147 institutionalised elderly patients. 37 Urine phosphate was lower in the March to August period of the year in 118 male stone formers on a "free diet" reported by Juuti et al 38 …”
mentioning
confidence: 89%